Some Aspects of English Competency Based Curriculum - A Halim Majid (Jurnal Dedikasi Pendidikan, 2018)
Talking about curriculum, since 1954 there have been several changes implemented in Indonesian schools with different emphases and purposes, but at least they share one common objective—to improve the quality of learning process in Indonesian education. However, the constraint is still on the result of the implementation of those curricula themselves—the objectives were not optimally achieved. Of course, there are many factors that might affect. One factor that might affect is the understanding of teachers in interpreting the message carried by the curriculum. This article discusses the nature of the newly implemented curriculum—Competency-Based Curriculum, particularly on the nature of English subject. The discussion involves philosophical theoretical bases of English CBC, the characteristics of English curriculum, syllabus development, teaching, and learning assessment, and changes and challenges associated and with the implementation of the English CBC. By having a clear understanding of this curriculum, hopefully, teachers can interpret what the curriculum demands and try to implement it optimally so that the objectives can be successfully achieved.